Effect of basalt fiber distribution on the flexural–tensile rheological performance of asphalt mortar. (10th August 2018) - Zhang, Xiaoyuan; Gu, Xingyu; Lv, Junxiu
Highlights: A modified 3D model of fiber distribution is generated in a cuboid using MATLAB code. Models of three are selected to analyze the distribution effect. Flexural–tensile rheological value under the horizontal oriented fiber is minimum. Abstract: This paper proposes a new three-dimensional (3D) fiber distribution model to investigate the effect of basalt fiber (BF) distribution on the flexural–tensile rheological performance of asphalt mortar. BF-reinforced asphalt mortar (BFRAM) is assumed to consist of the asphalt mortar matrix and the BF. An algorithm of random BF distribution is introduced to generate a 3D numerical model using MATLAB code. The 3D numerical models of the three kinds of directional BF distribution, including vertical, 45° oblique, and horizontal orientation, are selected to analyze the fiber distribution effect and reinforcement mechanism. The BFRAM model is employed in a series of simulations of the bending beam creep test in ABAQUS to study the flexural–tensile rheological behavior. Results indicate that the flexural–tensile rheological deformation of the BFRAM model under different fiber distribution types is ranked in a decreasing order as follows: vertical, 45° oblique, random, and horizontal orientation fiber. The result of random distribution fiber is in excellent agreement with the testing value. The flexural–tensile strain for the vertical, 45° oblique, and horizontal orientation fiber models is reduced by approximately 26.7%, 33.6%, and 63.7% at 3600 s, respectively, compared with that of the control sample.